2014
DOI: 10.1002/app.41635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma treatment on the surface properties of polydimethylsiloxane

Abstract: In this work, the analysis of the plasma modification of polydimethylsiloxane (PDMS) substrates was conducted. The influence of the modification onto the changes occurred within the geometrical structure and chemical composition of the surface was analyzed. Due to the study of the atomic force microscopy, it was possible to determine the relationships between the surface development and applied process parameters, defining the conditions facilitating to obtain isotropic or anisotropic orientations of wrinkles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…In the case of the last, the most frequent processes include etching [ 16 , 32 , 33 ], cross-linking [ 16 , 34 , 35 ] and the deposition of thin coatings (e.g., DLC, gold or SiOx) [ 20 , 21 , 22 , 36 ]. Unfortunately, not all of the available modifications can produce stable properties for the surface, and their ageing manifests through a change in the water contact angle of the surface and its surface free energy [ 37 , 38 ]. When PDMS is, for instance, subject only to plasma pre-treatment, it is also necessary to determine the time and ageing rate of the surface, which is affected by various factors, including, in particular, the storage environment and the type and parameters of the modification [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the last, the most frequent processes include etching [ 16 , 32 , 33 ], cross-linking [ 16 , 34 , 35 ] and the deposition of thin coatings (e.g., DLC, gold or SiOx) [ 20 , 21 , 22 , 36 ]. Unfortunately, not all of the available modifications can produce stable properties for the surface, and their ageing manifests through a change in the water contact angle of the surface and its surface free energy [ 37 , 38 ]. When PDMS is, for instance, subject only to plasma pre-treatment, it is also necessary to determine the time and ageing rate of the surface, which is affected by various factors, including, in particular, the storage environment and the type and parameters of the modification [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, not all of the available modifications can produce stable properties for the surface, and their ageing manifests through a change in the water contact angle of the surface and its surface free energy [ 37 , 38 ]. When PDMS is, for instance, subject only to plasma pre-treatment, it is also necessary to determine the time and ageing rate of the surface, which is affected by various factors, including, in particular, the storage environment and the type and parameters of the modification [ 37 , 38 ]. The ageing effect is not observed after the production of DLC coatings on the PDMS substrate [ 16 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this procedure could reduce the amount of potential nucleation sites for AuTTF. Second, plasma treatment was found to damage the PDMS surface by creating cracks . A detailed inspection of the plasma‐treated surfaces by atomic force microscopy and scanning electron microscopy (SEM) revealed that the cracks were as deep as 18 nm and were visible all over the surface under the conditions used here (Figure S3 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 88%
“…The other two carbon peaks located at binding energies of ~286.1 eV and ~288 eV were associated with oxygen adsorbed on the coatings surface (Foong et al 2011;Takabayashi and Takahagi 2015). Thus, the results of XPS made it possible to evaluate the mutual share of sp 2 and sp Kaczorowski et al 2015). The quantitative analysis results of deconvoluted spectra are presented in Table 3.…”
Section: Materials Characteristicsmentioning
confidence: 99%